2015
DOI: 10.1088/0004-637x/809/1/40
|View full text |Cite
|
Sign up to set email alerts
|

Classifying X-Ray Binaries: A Probabilistic Approach

Abstract: In X-ray binary star systems consisting of a compact object that accretes material from an orbiting secondary star, there is no straightforward means to decide if the compact object is a black hole or a neutron star. To assist this classification, we develop a Bayesian statistical model that makes use of the fact that X-ray binary systems appear to cluster based on their compact object type when viewed from a 3-dimensional coordinate system derived from X-ray spectral data. The first coordinate of this data is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…We also found considerable overlap between HMXB and LMXB pulsars which suggests that the effect of the high magnetic fields in these systems outweighs the effect of the masses of their companions on their position in CCI diagrams. However, there is a significant difference between the range of fluxes displayed by HMXBs and LMXBs so they should be distinguishable using the machine learning technique of Gopalan et al (2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also found considerable overlap between HMXB and LMXB pulsars which suggests that the effect of the high magnetic fields in these systems outweighs the effect of the masses of their companions on their position in CCI diagrams. However, there is a significant difference between the range of fluxes displayed by HMXBs and LMXBs so they should be distinguishable using the machine learning technique of Gopalan et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…In a CCI diagram, the various classes of X-ray binaries -systems containing white dwarfs, neutron stars, or black holes -separate into complex, but geometrically distinct volumes. Using CCI diagrams, Gopalan et al (2015) developed a probabilistic (Bayesian) model which uses a supervised learning approach (unknown classifications are predicted using known classifications as priors), to predict the type of an unknown X-ray binary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that classifications made by their method tend to agree with classifications made with previously established classification techniques (e.g., by Saeedi et al 2016). Gopalan et al (2015) expanded the colour-colour-intensity diagram classification technique by applying a supervised learning algorithm as a method of demarcating systems containing black holes, pulsating neutron stars, or non-pulsating neutron stars. Lo et al (2014) employed the random forest algorithm to classify time-varying X-ray sources in the Second XMM-Newton Serendipitous Source Catalog using X-ray photometric time series and spectra and multiwavelength information.…”
Section: Machine Learning For X-ray Source Classificationmentioning
confidence: 99%
“…Machine learning has also been applied in the X-ray domain by Huppenkothen et al (2017) to classify light curves of the unusual BH X-ray binary GRS 1915+105. An effort to distinguish between different types of Xray binaries has been reported by Gopalan et al (2015), where they use a three-dimensional coordinate system comprising of colourcolour-Intensity diagrams to find clusters of data which can distinguish between BH and NS.…”
Section: Introductionmentioning
confidence: 99%